2020
DOI: 10.1080/07317115.2020.1839826
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Compassion Meditation Training to Improve Well-being Among Older Adults

Abstract: Objectives: Compassion meditation (CM) training has demonstrated potential in improving wellbeing and psychosocial functioning. However, most prior studies of CM training have focused on younger adults. The generalizability of the effectiveness of CM training with older adults requires further study. This pilot study was intended to inform future randomized controlled studies of CM training in older adults. Methods: Participants included 24 older adults who attended a 10-week group CM training. Exploratory out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Life satisfaction is an assessment of life as a whole (Diener et al, 1985), but it could be enhanced by a multiweek LKCM intervention (e.g., Malaktaris et al, 2020; Roca et al, 2021). Therefore, the underlying mechanism is worth noting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Life satisfaction is an assessment of life as a whole (Diener et al, 1985), but it could be enhanced by a multiweek LKCM intervention (e.g., Malaktaris et al, 2020; Roca et al, 2021). Therefore, the underlying mechanism is worth noting.…”
Section: Discussionmentioning
confidence: 99%
“…There are commonalities across meditation modalities, such as attention stability and learning to come back from distraction (e.g., Sheffield, 2017). Furthermore, LKCM is not easy for participants, and some LKCM training did not begin directly with LKCM but was based on mindfulness meditation (e.g., Krieger et al, 2016; Malaktaris et al, 2020). In addition, Fredrickson et al (2008) found that positive emotions steadily increased from the second week, indicating that it took practice to master the skill of loving‐kindness meditation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, concerns regarding the participants' ages are also relatively rare. Recently, sporadic studies have attempted to examine the effects of LKCM among elderly people (e.g., Malaktaris et al., 2022), and only a few studies have treated age as a moderator in post hoc ways (i.e., without a strong theoretical hypothesis; Kearney et al., 2021). With an increasing number of millennials, ageing people and women in the job market, it is necessary to consider practitioners' demographics when applying the LKCM in the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…In sum, as discussed by Araujo et al [66] the study of aging through the lens of positive psychology as proposed initially by Seligman [4] appears to allow both the practitioner or provider, as well as the client, to look beyond the decline normally associated with advancing age and to consider rewarding experiences and strategies that can help to promote a meaningful aging state, rather than one of despair, distress, despondency, and mood disorders. Moreover, addressed sooner rather than later, early interventions may not only help to ably preserve an optimal mental health status and well-being among aging adults, but may extend longevity [67,68], enhance compassion [69] along with increased feelings of love, closeness, or trust, while reducing negative feelings of stress, nervousness, and being overwhelmed, a finding also supported by Hodgetts et al [70] and Barton et al [71]. Smith et al [72] note that among older adults, a greater ability to savor positive experiences and higher resilience also predicted greater happiness, lower depression, and greater life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Significant increases in self-efficacy and morale are also anticipated [44], as are possible decreases in loneliness, and possible cognitive inflammatory states and physiological dysregulation [45], and depression [46]. Self-compassion May benefit mental health/life quality Kima nd Ko [58] Self-esteem Can protect against fears concerning loneliness Rossie et al [69] Spirituality + religion May slow cognitive decline in dementia Agli et al [60] Visualizing best self May help to increase/sustain positive emotion Sheldon et al [61] Zest for life May help avert depression Glasberg et al [62] Table 1. Sample of empowerment-based positive psychology strategies directed at emotional regulation, and the generation of positive self-perceptions, and beliefs and affect that can learned as well be applied alone or in combination ©2021 Ray Marks.…”
Section: What the Research Showsmentioning
confidence: 99%